World Bank East Asia and Pacific Economic Update, April 2021 : Uneven Recovery - World Bank (Washington, DC: World Bank, 2021)
A year after the first case was confirmed in Wuhan COVID-19 is proving hard to suppress even, while the emergence of more transmissible variants of the variant poses new challenges to the containment of the disease globally. The economies of the region began to bounce back in the second half of 2020. However, only China and Vietnam have followed a V-shape recovery path with output surpassing pre-COVID-19 levels. Most of the other countries have not seen a full-fledged recovery in terms of either output or growth momentum. Economic performance across countries continues to depend on (i) the efficiency with which the virus is contained; (ii) the ability to take advantage of the revival in international goods trade; and (iii) the capacity of governments to provide fiscal and monetary support. China and Vietnam are expected to enjoy strong growth in 2021, whereas other economies in the region will grow more gradually. Many economies, especially in the Pacific islands are not expected to reach pre-COVID-19 levels of output until 2022 or later. Governments in the region need to work cooperatively to address three key issues: (i) a regional and global distribution of vaccines that minimizes the risk of a continued spread of COVID-19 and its variants; (ii) continue to provide economic support to their economies while carefully evaluating the trade-offs between the need for further stimulus and debt sustainability; and (iii) enact policies and prioritize investments that protect against climate risk to ensure sustainable economic growth.